Fischer-tropsch synthesis catalyst, method for preparing the same, and method for fischer-tropsch synthesis reaction
Patent Information
- Application Number
- CN202510425426.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-04-07
- Publication Date
- 2026-10-16
AI Technical Summary
[0006]本发明的目的是为了克服现有技术存在的蜂窝形催化剂的机械强度较差、催化剂难以兼顾传质扩散能力的问题,提供一种费托合成催化剂及其制备方法、费托合成反应的方法,该催化剂具有较高的机械强度,以及较高的CO转化率和C5+烃类选择性
[0019](1) The Fischer-Tropsch synthesis catalyst provided by this invention has high mechanical strength, as well as high CO conversion and C5 concentration. + Hydrocarbon selectivity;
Smart Images

Figure BDA0005346578910000191 
Figure BDA0005346578910000201 
Figure BDA0005346578910000211
Abstract
Description
Technical Field
[0001] This invention relates to the field of catalyst technology, specifically to a Fischer-Tropsch synthesis catalyst and its preparation method, as well as a method for the Fischer-Tropsch synthesis reaction. Background Technology
[0002] The Fischer-Tropsch synthesis is a gas-solid-liquid multiphase reaction system. In a fixed-bed reactor, the catalyst particle size is typically a few millimeters, making diffusion control an unavoidable factor affecting catalytic activity. During the internal diffusion of reactants, H2 diffuses faster than CO. Due to the difference in particle size, a difference in CO concentration gradient occurs within the particle, affecting the binding of CO to the metal active sites. This increases the H / C ratio adsorbed at the active sites, reduces the probability of carbon chain growth, and lowers the C content. 5+ The selectivity of CO is thus improved. Therefore, improving the mass transfer of CO within the particle is beneficial to enhancing the overall conversion behavior within the particle and the selectivity of heavy hydrocarbons. Eggshell-type catalysts exhibit unique performance in reducing the diffusion limitation of key components.
[0003] A wide variety of support materials are suitable for use as Fischer-Tropsch synthesis catalysts, including alumina, silica, silica-alumina, zinc oxide, titanium dioxide, zirconium oxide, activated carbon, and mesoporous molecular sieves, as well as supports modified with additives and mixtures thereof. Regarding alumina supports, due to their strong hydrophilicity and high isoelectric point, the alumina surface readily adsorbs anions in acidic cobalt nitrate solutions. Furthermore, when a highly hydrophilic alumina support is directly immersed in the impregnation solution, capillary pressure is generated due to surface tension, causing the liquid to penetrate into the capillary, and the active component subsequently permeates into the support. Both of these factors increase the difficulty of preparing eggshell-shaped catalysts with alumina as the support using the impregnation method.
[0004] CN105233880A discloses a core-type clover-shaped catalyst support, its preparation method, and its application. The catalyst support includes a catalyst support rod, which comprises an outer shell and an inner core. The outer shell has a hollow clover-shaped cross-section, and the inner core fills the hollow portion of the outer shell. The outer shell is made of a porous material, and the inner core is made of a dense material with a specific surface area <1 m². 2 / g. However, the bonding strength between the two materials at the interface needs to be verified.
[0005] Therefore, a catalyst for Fischer-Tropsch synthesis that combines high mechanical strength, simple preparation, and high mass transfer and diffusion capability is needed. Summary of the Invention
[0006] The purpose of this invention is to overcome the problems of poor mechanical strength and difficulty in simultaneously achieving mass transfer and diffusion capabilities in existing honeycomb catalysts, and to provide a Fischer-Tropsch synthesis catalyst, its preparation method, and a method for the Fischer-Tropsch synthesis reaction. This catalyst exhibits high mechanical strength, as well as high CO conversion and C20 concentrations. 5+ Hydrocarbon selectivity.
[0007] To achieve the above objectives, a first aspect of the present invention provides a Fischer-Tropsch synthesis catalyst, wherein the catalyst is a honeycomb catalyst comprising a support and an active component, the active component comprising cobalt and / or ruthenium;
[0008] The active component, based on the total mass of the catalyst and the amount of oxides, has a mass percentage content of 2-24 wt%; the catalyst support has an average mechanical strength of 10-30 N / mm.
[0009] The particle mechanical strength dispersion coefficient of the catalyst support is in the range of 0-0.58.
[0010] A second aspect of the present invention provides a method for preparing a Fischer-Tropsch synthesis catalyst, wherein the method includes the following steps:
[0011] (1) The carrier precursor is mixed with a peptide solvent to obtain a mixture;
[0012] (2) After the mixture is subjected to a first mixing and / or a first molding, a second mixing, a second molding and calcination are performed to obtain a catalyst support;
[0013] (3) The catalyst support is contacted with a solution containing the active component and calcined to obtain the Fischer-Tropsch synthesis catalyst;
[0014] The active component is cobalt and / or ruthenium; the conditions for the second molding include: molding temperature of 20-60℃, molding pressure of 3-10MPa, and material temperature change before and after the second molding of less than 10℃.
[0015] The amount of the solution containing the active component is such that, based on the total mass of the catalyst and in terms of oxides, the mass percentage of the active component is 2-24 wt%.
[0016] The third aspect of the present invention provides a Fischer-Tropsch synthesis catalyst prepared by the preparation method described in the second aspect.
[0017] A fourth aspect of the present invention provides a method for Fischer-Tropsch synthesis, wherein the method comprises: carrying out a Fischer-Tropsch synthesis reaction on reactants in the presence of a catalyst described in the first or third aspect.
[0018] The beneficial effects achieved through the above technical solution are as follows:
[0019] (1) The Fischer-Tropsch synthesis catalyst provided by this invention has high mechanical strength, as well as high CO conversion and C5 concentration. + Hydrocarbon selectivity;
[0020] (2) In this invention, preferably, the preparation method of the Fischer-Tropsch synthesis catalyst is simple, which improves the mechanical strength of the honeycomb catalyst support while ensuring the high specific surface area and high pore volume of the catalyst, which is beneficial to the loading and dispersion of the active components, thereby giving the catalyst of this invention high catalytic activity and selectivity. Detailed Implementation
[0021] The endpoints and any values of the ranges disclosed herein are not limited to the precise ranges or values, and these ranges or values should be understood to include values close to these ranges or values. For numerical ranges, the endpoint values of the various ranges, the endpoint values of the various ranges and individual point values, and individual point values can be combined with each other to obtain one or more new numerical ranges, which should be considered as specifically disclosed herein.
[0022] The first aspect of the present invention provides a Fischer-Tropsch synthesis catalyst, wherein the catalyst is a honeycomb catalyst comprising a support and an active component, the active component comprising cobalt and / or ruthenium;
[0023] The active component, based on the total mass of the catalyst and the amount of oxides, has a mass percentage content of 2-24 wt%.
[0024] The average mechanical strength of the catalyst support is 10-30 N / mm;
[0025] The particle mechanical strength dispersion coefficient of the catalyst support is in the range of 0-0.58.
[0026] Fischer-Tropsch synthesis is a strongly exothermic reaction. To meet the exothermic requirement of Fischer-Tropsch synthesis, honeycomb catalysts are usually used. Conventional honeycomb catalysts have high specific surface area and high pore volume, but poor mechanical strength. The catalyst support provided by this invention has high specific surface area and high pore volume, while ensuring high average mechanical strength. The mechanical strength of the support is concentrated.
[0027] According to the present invention, preferably, the average mechanical strength of the catalyst support is 10-30 N / mm, for example 10 N / mm, 12 N / mm, 14 N / mm, 16 N / mm, 18 N / mm, 20 N / mm, 22 N / mm, 24 N / mm, 26 N / mm, 28 N / mm, 30 N / mm, or any range between the two, preferably 15-30 N / mm.
[0028] In this invention, the average mechanical strength refers to the average value calculated from the compressive strength tested on 22 catalyst support particles. The compressive strength is obtained by measuring the crushing mechanical strength.
[0029] According to the present invention, preferably, the particle mechanical strength dispersion coefficient of the catalyst support is in the range of 0-0.58, for example, 0, 0.05, 0.1, 0.15, 0.2, 0.25, 0.3, 0.35, 0.4, 0.45, 0.5, or any range between the two, preferably in the range of 0-0.45.
[0030] In this invention, the dispersion coefficient refers to the mechanical strength dispersion of the catalyst support particles, which is the ratio of the standard deviation of the mechanical strength values of a set of catalyst support particles to their average value. The number of catalyst support particles is n, which is 15-30.
[0031] According to the present invention, preferably, the specific surface area of the catalyst support is 100-260 m². 2 / g, for example, 100m 2 / g、110m 2 / g, 120m 2 / g, 130m 2 / g, 140m 2 / g, 150m 2 / g, 160m 2 / g、170m 2 / g、180m 2 / g、200m 2 / g、220m 2 / g、240m 2 / g、260m 2 / g, or any range between the two, preferably 110-150m 2 / g.
[0032] According to the present invention, preferably, the pore volume of the catalyst support is 0.4-0.7 mL / g, for example 0.4 mL / g, 0.45 mL / g, 0.5 mL / g, 0.55 mL / g, 0.6 mL / g, 0.65 mL / g, 0.7 mL / g, or any range between the two, preferably 0.45-0.6 mL / g. In the present invention, the specific surface area and pore volume of the catalyst support are measured by the BET low-temperature nitrogen adsorption method.
[0033] According to the present invention, the type of catalyst support is not particularly limited, as long as the specific surface area, pore volume, and average mechanical strength of the support meet the defined range. Preferably, the catalyst support is selected from at least one of alumina, silica, alumina-silica, molecular sieve, zirconium oxide, zinc oxide, and titanium oxide, with alumina being the most preferred.
[0034] In this invention, the structural dimensions of the catalyst support are not particularly limited, as long as they meet the requirements for a honeycomb support. Preferably, the particle diameter of the catalyst support is 3-20 mm, more preferably 3.5-17 mm. Catalyst supports with smaller particle diameters are easier to mold and achieve high mechanical strength; the larger the particle diameter, the more difficult it is to improve mechanical strength. In this invention, the catalyst support achieves high specific surface area, high pore volume, and high mechanical strength while having a relatively large particle diameter.
[0035] In this invention, the particle diameter of the catalyst support is measured by measuring the diameter of the circumscribed circle of the support cross-section.
[0036] According to the present invention, preferably, the catalyst support further comprises a modifying agent component, wherein the modifying agent component is selected from at least one of La, Zr, Ce, and W. In the present invention, the addition of the modifying agent component can increase the specific surface area and pore volume of the catalyst support, while simultaneously improving the mechanical strength of the catalyst support.
[0037] According to the present invention, preferably, the modified auxiliary component, based on the total mass of the catalyst support and based on the oxide, has a mass percentage content of 0-17 wt%, for example, 0.001 wt%, 0.002 wt%, 0.005 wt%, 0.01 wt%, 0.02 wt%, 0.05 wt%, 0.06 wt%, 0.1 wt%, 0.2 wt%, 0.5 wt%, 1 wt%, 2 wt%, 3 wt%, 4 wt%, 5 wt%, 6 wt%, 7 wt%, 8 wt%, 9 wt%, 10 wt%, 12 wt%, 15 wt%, 17 wt%, or any range between the two, preferably 0.001-10 wt%, more preferably 1-5 wt%.
[0038] According to the present invention, preferably, the mass percentage of the active component, based on the total mass of the catalyst and based on oxides, is 5-18 wt%, for example, 5 wt%, 6 wt%, 7 wt%, 8 wt%, 9 wt%, 10 wt%, 11 wt%, 12 wt%, 13 wt%, 14 wt%, 15 wt%, 16 wt%, 17 wt%, 18 wt%, or any range between the two. In the present invention, the active component in the catalyst is supported on a catalyst support with high mechanical strength and high specific surface area, and is uniformly dispersed, exhibiting high catalytic activity and selectivity.
[0039] According to the present invention, preferably, when the active component is cobalt, the catalyst further comprises a reduction aid component, wherein the reduction aid component is selected from at least one of Re, Ru, Rh, Pd, Os, Ir, Pt, Ag and Au.
[0040] In this invention, when the catalyst contains both cobalt and ruthenium, if the ruthenium content is less than 0.5 wt% by element, ruthenium is used as a reducing aid component; if the ruthenium content is not less than 0.5 wt%, ruthenium is used as an active component.
[0041] According to the present invention, preferably, the mass percentage of the reducing agent component, based on the total mass of the catalyst and in terms of elements, is 0-0.5 wt%, for example, 0.001 wt%, 0.002 wt%, 0.005 wt%, 0.01 wt%, 0.02 wt%, 0.03 wt%, 0.05 wt%, 0.06 wt%, 0.08 wt%, 0.1 wt%, 0.12 wt%, 0.15 wt%, 0.18 wt%, 0.2 wt%, 0.25 wt%, 0.3 wt%, 0.35 wt%, 0.4 wt%, 0.45 wt%, 0.5 wt%, or any range between the two, preferably 0.005-0.3 wt%.
[0042] In this invention, preferably, the addition of the reducing agent component can help lower the reduction temperature of the catalyst. In this invention, the mass percentage of the active component, the modified agent component, and the reducing agent component is determined by X-ray fluorescence spectrometry. In the catalyst, the reducing agent component exists in an oxidized state; for ease of measurement, the content of the reducing agent component is expressed as an element.
[0043] In this invention, preferably, the catalyst uses cobalt as the active component and lanthanum and / or cerium as the modifying agent component. It has a high content of active components, high mechanical strength with a concentrated strength distribution, and also possesses high specific surface area and high pore volume. This results in high CO conversion and C5 concentration during the Fischer-Tropsch synthesis process. + Hydrocarbon selectivity.
[0044] A second aspect of the present invention provides a method for preparing a Fischer-Tropsch synthesis catalyst, wherein the method includes the following steps:
[0045] (1) The carrier precursor is mixed with a peptide solvent to obtain a mixture;
[0046] (2) After the mixture is subjected to a first mixing and / or a first molding, a second mixing, a second molding and calcination are performed to obtain a catalyst support;
[0047] (3) The catalyst support is contacted with a solution containing the active component and calcined to obtain the Fischer-Tropsch synthesis catalyst;
[0048] The active component is cobalt and / or ruthenium; the conditions for the second molding include: molding temperature of 20-60℃, molding pressure of 3-10MPa, and material temperature change before and after the second molding of less than 10℃.
[0049] The amount of the solution containing the active component is such that, based on the total mass of the catalyst and in terms of oxides, the mass percentage of the active component is 2-24 wt%.
[0050] In this invention, preferably, the preparation method is simple and the conditions are controllable. It improves the mechanical strength of the honeycomb catalyst support while ensuring a high specific surface area and high pore volume of the catalyst, which is beneficial for the loading and dispersion of the active components. Therefore, the catalyst of this invention possesses excellent mass and heat transfer performance, high catalytic activity, and C5... + Selectivity.
[0051] In this invention, the molding temperature is controlled within a relatively low temperature range to avoid molding at higher temperatures, which would result in uneven heating of the outer surface and interior of the molded product particles, with the outer surface temperature being too high and the interior temperature being too low, thus reducing the mechanical strength of the catalyst support.
[0052] According to the present invention, preferably, the carrier precursor is a substance that is converted into a carrier through calcination. In this invention, the source of the carrier precursor is not particularly limited; those skilled in the art can choose conventional carrier precursors, which can be commercially available or prepared by existing methods, as long as they can be converted into a carrier after calcination.
[0053] According to the present invention, preferably, the support is selected from at least one of alumina, silica, molecular sieve, zirconium oxide, zinc oxide, and titanium oxide. The support precursor is selected from at least one of hydrated alumina, alumina colloid, zeolite, kaolin, silica, zirconium oxide, zinc oxide, and titanium oxide. According to a preferred embodiment of the present invention, the support precursor is boehmite and / or molecular sieve.
[0054] In this invention, preferably, alumina has the characteristics of large specific surface area, controllable pore structure, good thermal stability and strong adsorption capacity. Using boehmite as a precursor to prepare the catalyst support, the resulting catalyst support has a higher specific surface area and pore volume, which is beneficial to the loading and dispersion of active components. Further preparation of the catalyst results in higher catalytic activity.
[0055] According to the present invention, preferably, the colloidal solvent is an organic acid compound and / or an inorganic acid compound, preferably selected from at least one of nitric acid, aluminum nitrate, acetic acid, and citric acid, and more preferably a mixture of nitric acid and citric acid. In the present invention, the addition of the colloidal solvent enables sufficient colloidal dissolution between the precursor particles, improving the mechanical strength of the formed catalyst support and improving the pore structure. The type of colloidal solvent is not particularly limited in the present invention, and can be any colloidal solvent conventionally used in the art.
[0056] According to the present invention, preferably, the amount of the adhesive solvent added is 0.4-10 parts by weight, more preferably 0.6-8 parts by weight, relative to 100 parts by weight of the carrier precursor. In this invention, controlling the amount of adhesive solvent added within the above range avoids insufficient addition of adhesive solvent, resulting in inadequate dissolution of the catalyst carrier, and excessive addition of adhesive solvent, leading to excessive acidity of the catalyst carrier and weakened mechanical strength.
[0057] According to the present invention, preferably, in step (1), the mixture further includes a solvent and a modifying agent. The type and source of the solvent are not particularly limited, but water is preferred.
[0058] According to the present invention, preferably, the volume of solvent used is 0.6-1 mL, more preferably 0.65-0.95 mL, based on 1 g of the carrier precursor.
[0059] According to the present invention, preferably, the modifying agent is a water-soluble compound selected from at least one of La, Zr, Ce, and W, and more preferably selected from at least one of lanthanum nitrate, cerium nitrate, ammonium metatungstate, and zirconium nitrate. Using the above-mentioned modifying agent in combination with the support precursor and the colloidal solvent improves the stability of the support precursor, making it less prone to phase transformation after calcination, and helps to increase the specific surface area and pore volume of the catalyst support without affecting its mechanical strength.
[0060] According to the present invention, preferably, the amount of the modifying agent added relative to 100 parts by weight of the carrier precursor is 0-15 parts by weight, for example 0.6 parts by weight, 0.8 parts by weight, 1 part by weight, 1.5 parts by weight, 2 parts by weight, 3 parts by weight, 4 parts by weight, 5 parts by weight, 6 parts by weight, 8 parts by weight, 10 parts by weight, 12 parts by weight, 15 parts by weight, or any range between the two, preferably 0.8-12 parts by weight, more preferably 1-8 parts by weight.
[0061] In this invention, preferably, an extrusion aid, a binder, and a lubricant are also added in step (1).
[0062] According to the present invention, the type of extrusion aid is not particularly limited, and can be a conventional extrusion aid in the art, preferably guar gum powder and / or cellulose. The amount of the extrusion aid is not particularly limited, and those skilled in the art can make adaptive adjustments as needed to ensure smooth subsequent molding. Preferably, the amount of the extrusion aid added relative to 100 parts by weight of the carrier precursor is 0-8 parts by weight, more preferably 0-6 parts by weight.
[0063] In this invention, preferably, the binder is an inorganic binder and / or an organic binder. The binder can function as a binder for the carrier precursor particles.
[0064] In this invention, the type of inorganic binder is not particularly limited and can be any conventional inorganic binder in the art. Preferably, the inorganic binder is selected from at least one of cement, alumina sol, silica sol, zirconium sol, and titanium sol.
[0065] In this invention, the type of organic binder is not particularly limited and can be any conventional organic binder in the art. Preferably, the organic binder is selected from at least one of methylcellulose, ethylcellulose, hydroxypropylcellulose, hydroxypropyl methylcellulose, and microcrystalline cellulose.
[0066] According to the present invention, the amount of adhesive used is not particularly limited, and those skilled in the art can adapt the addition of adhesive and the amount of adhesive added according to the mixing situation. Preferably, the amount of adhesive added is 0-4 parts by weight, more preferably 0-3 parts by weight, relative to 100 parts by weight of the carrier precursor.
[0067] According to the present invention, the type of lubricant is not particularly limited and can be any conventional lubricant in the art. Those skilled in the art can select the type and amount of lubricant according to the molding effect. Preferably, the lubricant is selected from at least one of glycerin, polyol, polyester, magnesium stearate, stearic acid, talc, and graphite.
[0068] According to the present invention, preferably, the amount of lubricant added is 0-10 parts by weight, more preferably 0-5 parts by weight, relative to 100 parts by weight of the carrier precursor. In the present invention, the addition of lubricant has a lubricating effect, which facilitates the smooth progress of molding and, combined with the molding conditions, can improve the average mechanical strength of the catalyst carrier.
[0069] According to a preferred embodiment of the present invention, the mixing process includes: dry mixing the carrier precursor with the extrusion aid, binder and lubricant for a certain period of time, and then adding an aqueous solution containing the modifier and the adhesive solvent to mix the above raw materials evenly.
[0070] According to the present invention, preferably, step (1) the first mixing includes dry mixing, kneading and / or rolling.
[0071] According to the present invention, preferably, the conditions for the first mixing include: a mixing time of 10-80 min, preferably 20-60 min.
[0072] According to the present invention, preferably, the conditions for the first molding include: a molding temperature of 20-60°C, more preferably 30-50°C; and a molding pressure of 3-10 MPa, more preferably 5-8 MPa.
[0073] According to a preferred embodiment of the present invention, the first molding is selected from at least one of extrusion molding, compression molding, and ball forming. Those skilled in the art can choose conventional molding equipment to perform the molding.
[0074] In this invention, preferably, extrusion molding is used to obtain a catalyst support with high specific surface area and pore volume while also having high mechanical strength, resulting in high preparation efficiency.
[0075] In this invention, the shape of the product obtained by the first extrusion molding is not particularly limited. Preferably, it is selected from at least one of butterfly shape, cylindrical shape, clover shape, honeycomb shape, Raschig ring shape, and porous profile. According to the present invention, preferably, the second mixing in step (2) includes kneading and / or rolling.
[0076] According to the present invention, preferably, the conditions for the second mixing include: a mixing time of 20-60 min, more preferably 30-50 min.
[0077] According to the present invention, preferably, the conditions for the second molding include: molding temperature of 30-50°C; molding pressure of 5-8.5 MPa.
[0078] According to a preferred embodiment of the present invention, the total time for the first mixing and the second mixing is 30-120 minutes.
[0079] According to the present invention, preferably, the conditions for the first molding include: molding temperature of 30-50°C; molding pressure of 5-8 MPa.
[0080] In this invention, preferably, the temperature change of the material before and after the first molding is less than 15°C.
[0081] According to the present invention, preferably, the temperature change of the material before and after the second molding is less than 8°C. In the present invention, the temperature change of the material before and after molding, taking extrusion molding as an example, refers to the difference between the temperature of the material entering the extruder (i.e., the molding temperature) and the temperature of the material after extrusion.
[0082] In this invention, preferably, the second molded product is formed by extrusion molding. The product obtained by the second extrusion molding has a honeycomb shape, which has better heat dissipation performance, and the resulting catalyst support has a higher specific surface area and pore volume.
[0083] In this invention, preferably, the product of the second molding is dried before calcination. The drying conditions are not particularly limited, and those skilled in the art can choose conventional drying methods and conditions. Preferably, the drying conditions include: a drying temperature of 45-160℃, more preferably 70-140℃; and a drying time of 1-80 hours, more preferably 2-70 hours.
[0084] According to the present invention, preferably, the calcination conditions include: a calcination temperature of 450-1200℃, more preferably 600-1000℃; and a calcination time of 1-8 hours, more preferably 2-6 hours.
[0085] According to the present invention, the source of the active component is not particularly limited, but is preferably a water-soluble compound of cobalt and / or ruthenium, such as at least one selected from cobalt nitrate, cobalt acetate, cobalt carbonyl and ruthenium chloride, and ruthenium nitrite.
[0086] According to the present invention, preferably, the amount of the solution containing the active component is such that, based on the total mass of the catalyst and as an oxide, the mass percentage of the active component is 2-24 wt%, preferably 5-18 wt%. In the present invention, the high content of the active component in the catalyst helps to improve the reactivity of the Fischer-Tropsch synthesis reaction, increase CO conversion, and reduce methane selectivity.
[0087] In this invention, preferably, the molar concentration of the active component in the solution containing the active component is 0.5-6 mol / L, more preferably 2-4 mol / L.
[0088] In this invention, the volume of the solution containing the active component added is not particularly limited, as long as the content of the active component in the catalyst meets the above-mentioned range. Preferably, based on 1g of the mass of the catalyst support, the volume of the solution containing the active component is 0.5-2mL, more preferably 0.6-1.5mL.
[0089] According to the present invention, preferably, when the active component is cobalt, the solution containing the active component in step (3) further includes a reducing agent.
[0090] According to the present invention, preferably, the reducing agent is a water-soluble compound containing a reducing agent component. More preferably, it is at least one of chloride, nitrate, chlorate, and acid compounds containing a reducing agent component.
[0091] According to the present invention, preferably, the reducing agent component is selected from at least one of Re, Ru, Rh, Pd, Os, Ir, Pt, Ag and Au.
[0092] In this invention, preferably, the reducing agent is selected from at least one of perrhenic acid, platinum ammonia, chloroplatinic acid, and nitrosylruthenium nitrate.
[0093] According to the present invention, preferably, the amount of the reducing agent is such that, based on the total mass of the catalyst and in terms of elemental composition, the mass percentage of the reducing agent component is 0-0.5 wt%, preferably 0.005-0.3 wt%. In this invention, introducing a certain amount of the reducing agent component helps to lower the reduction temperature of the catalyst during the Fischer-Tropsch synthesis reaction.
[0094] According to a preferred embodiment of the present invention, when the solution containing the active component contains both cobalt and ruthenium, the ruthenium content is less than 0.5 wt% based on the total mass of the catalyst and is used as a reducing aid component, while the ruthenium content is not less than 0.5 wt% based on the elemental content.
[0095] In this invention, the contact conditions are not particularly limited. According to a preferred embodiment of the invention, the catalyst support is impregnated in a solution containing the active component and then dried to obtain the catalyst. The impregnation time is 1-8 hours, preferably 3-5 hours.
[0096] In this invention, the drying conditions are not particularly limited, but preferably the drying conditions include: a drying temperature of 100-160℃ and a drying time of 1-5h.
[0097] According to the present invention, preferably, the calcination conditions in step (3) include: a calcination temperature of 200-500℃, preferably 250-400℃; and a calcination time of 1-12 hours, preferably 2-5 hours.
[0098] The third aspect of the present invention provides a Fischer-Tropsch synthesis catalyst prepared by the preparation method described in the second aspect.
[0099] A fourth aspect of the present invention provides a method for Fischer-Tropsch synthesis, wherein the method comprises: carrying out a Fischer-Tropsch synthesis reaction on reactants in the presence of a catalyst described in the first or third aspect.
[0100] In this invention, the catalyst exhibits high catalytic activity and high C content in the Fischer-Tropsch synthesis reaction. 5+ Hydrocarbon selectivity can reduce the selectivity of carbon dioxide and methane.
[0101] According to the catalyst provided by the present invention, the oxidized active metal component is reduced and activated before use. The conditions for reduction and activation may include: under a hydrogen-containing atmosphere, the reduction temperature may be 200°C to 900°C, preferably 250°C to 750°C, and the reduction time may be 1-96 hours, preferably 2-24 hours.
[0102] In this invention, preferably, the hydrogen-containing atmosphere is hydrogen and / or a mixture of hydrogen and an inert gas. The inert gas refers to a gas that does not participate in the chemical reaction under the conditions of this invention, such as nitrogen and group zero element gases. If the reaction is carried out in a mixture of hydrogen and nitrogen, the hydrogen pressure can be 0.1-4 MPa, preferably 0.1-2 MPa.
[0103] According to the present invention, the conditions for the Fischer-Tropsch synthesis reaction are not particularly limited, but are preferably carried out in a fixed-bed reactor. The reaction conditions include: specifically, a temperature of 170-350°C, preferably 180-330°C; a total pressure of 1-20 MPa, preferably 1.5-15 MPa; and a gas hourly space velocity (GHSV) of syngas of 500-10000 h⁻¹. -1 Preferably 1000-8000h -1 .
[0104] In this invention, the reactants for the Fischer-Tropsch synthesis reaction include H2 and CO. The H2 / CO molar ratio is not particularly limited, as long as it can carry out the Fischer-Tropsch synthesis reaction. Preferably, the H2 / CO molar ratio is 1-2.
[0105] The present invention will be described in detail below through examples and comparative examples. Unless otherwise specified, all reagents used in the following examples and comparative examples are commercially available.
[0106] The relative molecular weight of methylcellulose is 450 g / mol;
[0107] The screw extruder was purchased from the South China University of Technology Science and Technology Industrial Plant, model F-26.
[0108] Carrier Preparation Example 1
[0109] (1) Mix 200g of boehmite powder (purchased from Sasol, alumina dry basis mass fraction of 75%) and 6g of guar gum powder for 10min. Add 1wt% nitric acid (mass concentration of 63wt%) and 1wt% citric acid relative to the mass of boehmite powder as a gel solvent. Then add water to dissolve and make up to volume to obtain a mixture. The ratio of the total volume of water added to the mixture (in mL) to the mass of boehmite powder (in g) is 0.78.
[0110] (2) Mix the above mixture for 20 minutes until it is uniform. Extrude the mixture into a 4 mm butterfly strip in a screw extruder. The first molding temperature is 45℃, the molding pressure is 7.2 MPa, and the material temperature changes by 12℃ before and after molding to obtain the extruded strip.
[0111] Add 15 grams of water to the extruder strip and continue mixing for 30 minutes. The resulting material is then extruded on a screw extruder using a honeycomb perforated plate to form honeycomb strips with a diameter of 5 mm, a wall thickness of 1.8 mm, an internal through-hole wall thickness of 0.4 mm, and a through-hole spacing of 0.4 mm. The second molding temperature is controlled at 42℃, the molding pressure at 7.8 MPa, and the material temperature change before and after molding is 6℃, resulting in the molded product.
[0112] The molded product was dried at 120°C for 4 hours and then calcined at 960°C for 4 hours to obtain catalyst support A1. The physical properties are shown in Table 1.
[0113] Carrier preparation Comparative Example 1
[0114] The catalyst support was prepared according to the method of support preparation example 1, except that the mixture in step (1) was kneaded for 15 min and then directly extruded on a screw extruder using a honeycomb perforated plate to form honeycomb strips with a diameter of 5 mm, a wall thickness of 1.8 mm, an internal through-hole wall thickness of 0.4 mm, and a through-hole spacing of 0.4 mm. The molding temperature was 45 °C, the molding pressure was 7.2 MPa, and the material temperature change before and after molding was 12 °C to obtain the molded product. The product was dried and calcined to obtain catalyst support D1. Other conditions were the same as in support preparation example 1. The physical property parameters are shown in Table 1.
[0115] Carrier preparation Comparative Example 2
[0116] The catalyst support was prepared according to the method of support preparation example 1, except that the molding temperature of the first molding and the second molding was controlled at 70°C, and other conditions were the same as in example 1. The resulting catalyst support D2 and the physical property parameters of the support are shown in Table 1.
[0117] Carrier Preparation Example 2
[0118] (1) Mix 200g of boehmite powder (purchased from Sasol, alumina dry basis mass fraction of 75%) and 6g of guar gum powder for 10min. Add 0.8wt% nitric acid (mass concentration of 63wt%) and 1.5wt% citric acid relative to the mass of boehmite powder as a gel solvent. Add water to make up the volume to obtain a mixture. The ratio of the total volume of water added (in mL) to the mass of boehmite powder (in g) is 0.83.
[0119] (2) Mix the above mixture for 20 minutes until it is uniform. Extrude the mixture into a 4 mm butterfly strip on a screw extruder. The first molding temperature is 35℃, the molding pressure is 6.0 MPa, and the material temperature changes by 5℃ before and after molding to obtain the extruded strip.
[0120] The extruded strips were further mixed and milled for 30 minutes. The resulting material was then extruded into honeycomb strips with a diameter of 5 mm, a wall thickness of 1.8 mm, an internal through-hole wall thickness of 0.4 mm, and a through-hole spacing of 0.4 mm using a honeycomb perforated plate on a screw extruder. The second molding temperature was controlled at 35℃, the molding pressure at 8.1 MPa, and the material temperature change before and after molding was 7℃, resulting in the molded product. The molded product was dried at 120℃ for 4 hours and then calcined at 960℃ for 4 hours to obtain catalyst support A2. The physical properties are shown in Table 1.
[0121] Carrier preparation example 3
[0122] The method of Preparation Example 1 was followed, except that (1) 200 g of boehmite powder (purchased from Sasol, alumina dry basis mass fraction of 75%) and 6 g of guar gum powder were mixed for 10 min, and 1 wt% nitric acid (mass concentration of 63 wt%) and 1 wt% citric acid (mass concentration of 1 wt%) relative to the mass of boehmite powder were added as a colloidal solvent, and 6 g of lanthanum nitrate, a modifying agent, were added. Then, water was added to dissolve and the mixture was brought to a final volume. The ratio of the total volume of water added to the mixture (in mL) to the mass of boehmite powder (in g) was 0.78. Other conditions were the same as in Preparation Example 1, and catalyst support A3 was obtained. The physical property data are shown in Table 1.
[0123] Carrier preparation example 4
[0124] (1) Mix 200g of boehmite powder (purchased from Sasol, alumina dry basis mass fraction of 75%) and 6g of guar gum powder evenly for 10min. Add 1.2wt% of nitric acid (mass concentration of 63wt%) relative to the mass of boehmite powder as a colloidal solvent, dissolve in water, add 4g of glycerol, add 12g of modified auxiliary zirconium nitrate, and then add water to make up the volume to obtain a mixture. The ratio of the total volume of water added to the mixture (in mL) to the mass of boehmite powder (in g) is 0.84.
[0125] (2) Knead the above mixture for 20 minutes to mix evenly, and then extrude the mixture into 4 mm butterfly strips on a screw extruder. The first molding temperature is 35℃, the molding pressure is 5.8MPa, and the material temperature change before and after molding is 5℃, thus obtaining the extruded strip.
[0126] Add 10g of water to the extruded strip and continue mixing for 30 minutes. The resulting material is then extruded onto a plunger extruder using a honeycomb perforated plate to form honeycomb strips with a diameter of 5mm, a wall thickness of 1.8mm, an internal through-hole wall thickness of 0.4mm, and a through-hole spacing of 0.4mm. The second molding temperature is controlled at 35℃, the material temperature change before and after molding is 8℃, and the molding pressure is 8.2MPa to obtain the molded product.
[0127] The molded product was dried at 120°C for 4 hours and then calcined at 960°C for 4 hours to obtain catalyst support A4. The physical properties are shown in Table 1.
[0128] Carrier preparation example 5
[0129] (1) 200 g of boehmite powder (purchased from Sasol, alumina dry basis mass fraction of 75%), 10 g of guar gum powder, and 1 g of methylcellulose were mixed evenly for 10 min. Nitric acid (mass concentration of 63 wt%) of 1.2 wt% relative to the mass of boehmite powder was added as a gel solvent. Water was added to dissolve the mixture. After adding 6 g of lanthanum nitrate as a modifier, water was added to make up the volume to obtain a mixture. The ratio of the total volume of water added to the mixture (in mL) to the mass of boehmite powder (in g) was 0.84.
[0130] (2) The above mixture was subjected to a first kneading and mixing process of 30 min and a second kneading and rolling process of 50 min, for a total of 80 min, until homogeneous. The resulting material was extruded onto a plunger extruder using a honeycomb perforated plate to form honeycomb strips with a diameter of 5 mm, a wall thickness of 1.8 mm, an internal through-hole wall thickness of 0.4 mm, and a through-hole spacing of 0.4 mm. The second molding temperature was controlled at 45℃, the molding pressure at 8.5 MPa, and the temperature change of the material before and after molding was 8℃, resulting in the molded product. The molded product was dried at 120℃ for 4 hours and then calcined at 1000℃ for 4 hours to obtain catalyst support A5. The physical property data are shown in Table 1.
[0131] Carrier preparation example 6
[0132] (1) 150 g of boehmite powder (purchased from Sasol, with an alumina dry basis mass fraction of 75%), 50 g of Siral 40 powder (purchased from Sasol, with a dry basis mass percentage of 80 wt%, of which silica dry basis accounts for 40% and the remainder is alumina dry basis), 6 g of guar gum powder, and 4 g of methylcellulose were mixed evenly for 10 min. Nitric acid (mass concentration of 63 wt%) with a mass relative to the boehmite powder was added, and the mixture was dissolved in water. After adding 6 g of lanthanum nitrate as a modifier, water was added to make up the volume to obtain a mixture. The ratio of the total volume of water added to the mixture (in mL) to the mass of boehmite powder (in g) was 0.78.
[0133] (2) The above mixture was first mixed for 20 min and then mixed for 60 min, and then combined and milled for 80 min until homogeneous. The resulting material was extruded on a plunger extruder using a perforated plate with a diameter of 5 mm, a wall thickness of 1.8 mm, an internal through-hole wall thickness of 0.4 mm, and a through-hole spacing of 0.4 mm. The second molding temperature was controlled at 40℃, the molding pressure at 8.6 MPa, and the temperature change of the material before and after molding was 8℃, to obtain the molded product. The molded product was dried at 120℃ for 4 hours and then calcined at 600℃ for 4 hours to obtain catalyst support A6. The physical property data are shown in Table 1.
[0134] Carrier Preparation Example 7
[0135] (1) 170 g of boehmite powder (purchased from Sasol, alumina dry basis mass fraction of 75%), 30 g of β molecular sieve (product of Changling Refinery Catalyst Plant, silicon-aluminum molar ratio (SiO2 / Al2O3 = 30, dry basis 87 wt%), 6 g of guar gum powder, and 2 g of methylcellulose were mixed evenly for 10 min. Nitric acid (mass concentration 63 wt%) and citric acid (1.2 wt% relative to the total mass of boehmite powder and β molecular sieve) were added. Water was added to make up to volume. The ratio of the total volume of water added (in mL) to the mass of boehmite powder (in g) was 0.84 to obtain a mixture.
[0136] (2) The above mixture was kneaded for 30 minutes in the first kneading process and rolled for 90 minutes in the second kneading process until it was uniformly mixed. Then, it was extruded on a plunger extruder using a perforated plate with a diameter of 6 mm, a wall thickness of 2 mm, an internal through-hole wall thickness of 0.4 mm, and a through-hole spacing of 0.4 mm for the second molding process. The second molding temperature was 30℃, the molding pressure was 8.6 MPa, and the material temperature change before and after molding was 9℃, resulting in a molded product. The molded product was dried at 120℃ for 4 hours and then calcined at 600℃ for 4 hours to obtain catalyst support A7. The physical property data are shown in Table 1.
[0137] Carrier preparation example 8
[0138] The catalyst was prepared according to the method of support preparation example 3, except that the temperature change of the material before and after the second molding in step (2) was controlled to be 10°C, and other conditions were the same as those in support preparation example 3. Catalyst support A8 was obtained, and the physical property parameters are shown in Table 1.
[0139] Carrier preparation example 9
[0140] The catalyst was prepared according to the method of support preparation example 3, except that 24g of lanthanum nitrate was added in step (1), and other conditions were the same as in support preparation example 3. Catalyst support A9 was obtained, and the physical property parameters are shown in Table 1.
[0141] Carrier Preparation Example 10
[0142] The catalyst was prepared according to the method of support preparation example 3, except that 6g of cerium nitrate was added as a modifier in step (1), and the other conditions were the same as those in support preparation example 3. Catalyst support A10 was obtained, and the physical property parameters are shown in Table 1.
[0143] Table 1 shows the test results of the physical properties of the catalyst support. The content of the modified additive components is calculated as oxides, based on the total weight of the catalyst support.
[0144] Table 1
[0145]
[0146] The average particle size and dispersion coefficient of the support were calculated using 22 catalyst supports.
[0147] As can be seen from the results in Table 1, the carrier prepared using the embodiments of the present invention has high mechanical strength, low coefficient of variation, large specific surface area and large pore volume, and thus has better practical performance as a carrier.
[0148] Example 1
[0149] 7.5 mL of a cobalt nitrate solution with a cobalt oxide molar concentration of 3.6 mol / L and 0.4 g of a perrhenic acid solution with a Re concentration of 0.35 wt% were mixed. 10 g of catalyst support was impregnated in the impregnation solution, stirred thoroughly, and then placed in a rotary evaporator for vacuum drying at 45 °C for 4 hours. Afterward, it was dried in an oven at 120 °C for 2 hours and calcined at 400 °C for 3 hours to obtain the catalyst. The obtained catalyst is denoted as C1, and its performance parameters are shown in Table 2.
[0150] Example 2-10
[0151] The active component and reducing agent were loaded according to the method of Example 1, except that the components of the loaded active component and reducing agent were adjusted. Other conditions were the same as in Example 1, and a catalyst was obtained. The support obtained in the comparative preparation example did not meet the practical requirements in terms of strength (the average mechanical strength of the support was less than 10 N / mm), so it was not used to prepare the catalyst and its activity was not evaluated.
[0152] The composition of the catalyst is shown in Table 2. The content of the active component in the catalyst is based on the total mass of the catalyst and is calculated as oxides; the content of the reducing agent component is based on the total mass of the catalyst and is calculated as elements.
[0153] Table 2
[0154]
[0155]
[0156] Note: / indicates that the corresponding substance was not added.
[0157] Test Example 1
[0158] The Fischer-Tropsch synthesis catalyst prepared in the example was packed into a fixed-bed reactor with a catalyst loading of 5 g. Hydrogen was injected at a flow rate of 1000 NL / g-cat / h (meaning a flow rate of 1000 standard liters per hour relative to one gram of catalyst) and heated to 400°C at a heating rate of 4°C / min, and held at that temperature for 5 hours.
[0159] Then, at 210℃ and 2.5MPa, for 2000h... -1 A mixture of H2 and CO (H2 / CO molar ratio of 2) is injected into the fixed-bed reactor at a gas space-time rate to carry out the Fischer-Tropsch synthesis reaction.
[0160] Catalytic performance was evaluated by analyzing the composition of the feed gas and reaction products in the fixed-bed reactor, and the CO conversion rate X was calculated. CO C 5+ Selectivity of hydrocarbons S C5+ Selectivity of CH4 CH4 and the selectivity of CO2 S CO2 The results are shown in Table 3 below.
[0161] Wherein, the conversion rate X of CO CO = Total number of moles of CO converted / Total number of moles of CO in the feed gas;
[0162] C 5+ Selectivity of hydrocarbons S C5+ = (Total moles of CO converted - Moles of carbon monoxide converted to carbon dioxide and C1-C4 hydrocarbons) / Total moles of CO converted;
[0163] CH4 selectivity S CH4 = Number of CO moles converted into CH4 / Total number of CO moles converted;
[0164] CO2 selectivity S CO2 = Number of CO moles converted into CO2 / Total number of CO moles converted.
[0165] Table 3
[0166]
[0167]
[0168] Note: The comparative sample does not meet the strength requirements and will not be used to prepare catalysts or for activity evaluation.
[0169] As can be seen from Table 3, the Fischer-Tropsch synthesis catalyst prepared by the method provided by the present invention exhibits high catalytic activity and CT content in the Fischer-Tropsch synthesis reaction. 5+ Hydrocarbon selectivity is low, and the selectivity for carbon dioxide and methane is also low.
[0170] The preferred embodiments of the present invention have been described in detail above; however, the present invention is not limited thereto. Within the scope of the inventive concept, various simple modifications can be made to the technical solutions of the present invention, including combinations of various technical features in any other suitable manner. These simple modifications and combinations should also be considered as the content disclosed in the present invention and are all within the protection scope of the present invention.
Claims
1. A Fischer-Tropsch synthesis catalyst, characterized in that, The catalyst is a honeycomb catalyst, comprising a support and an active component, wherein the active component comprises cobalt and / or ruthenium; The active component, based on the total mass of the catalyst and the amount of oxides, has a mass percentage content of 2-24 wt%. The average mechanical strength of the catalyst support is 10-30 N / mm; The particle mechanical strength dispersion coefficient of the catalyst support is in the range of 0-0.
58.
2. The catalyst according to claim 1, wherein, The catalyst support has an average mechanical strength of 15-30 N / mm; Preferably, the particle mechanical strength dispersion coefficient of the catalyst support is in the range of 0-0.45; Preferably, the specific surface area of the catalyst support is 100-260 m². 2 / g, preferably 110-150m 2 / g; Preferably, the pore volume of the catalyst support is 0.4-0.7 mL / g, more preferably 0.45-0.6 mL / g; Preferably, the catalyst support is selected from at least one of alumina, silica, alumina-silica, molecular sieve, zirconium oxide, zinc oxide, and titanium oxide.
3. The catalyst according to claim 1 or 2, wherein, The catalyst support further comprises a modifying agent component, wherein the modifying agent component is selected from at least one of La, Zr, Ce and W; Preferably, the modified additive component has a mass percentage content of 0-17 wt% based on the total mass of the catalyst support and based on the oxide content, more preferably 0.001-10 wt%, and more preferably 1-5 wt%.
4. The catalyst according to any one of claims 1-3, wherein, The active component, based on the total mass of the catalyst and the amount of oxides, is 5-18 wt% by mass. Preferably, when the active component is cobalt, the catalyst further comprises a reduction aid component, wherein the reduction aid component is selected from at least one of Re, Ru, Rh, Pd, Os, Ir, Pt, Ag and Au; Preferably, the mass percentage of the reducing agent component, based on the total mass of the catalyst and in terms of elements, is 0-0.5 wt%, more preferably 0.005-0.3 wt%.
5. A method for preparing a Fischer-Tropsch synthesis catalyst, characterized in that, The method includes the following steps: (1) The carrier precursor is mixed with a peptide solvent to obtain a mixture; (2) After the mixture is subjected to a first mixing and / or a first molding, a second mixing, a second molding and calcination are performed to obtain a catalyst support; (3) The catalyst support is contacted with a solution containing the active component and calcined to obtain the Fischer-Tropsch synthesis catalyst; The active component is cobalt and / or ruthenium; the conditions for the second molding include: molding temperature of 20-60℃, molding pressure of 3-10MPa, and material temperature change before and after the second molding of less than 10℃. The amount of the solution containing the active component is such that, based on the total mass of the catalyst and in terms of oxides, the mass percentage of the active component is 2-24 wt%.
6. The preparation method according to claim 5, wherein, The carrier precursor is a substance that is converted into a carrier through calcination; Preferably, the support is selected from at least one of alumina, silicon dioxide, molecular sieve, zirconium oxide, zinc oxide, and titanium dioxide; Preferably, the colloidal solvent is an organic acid compound and / or an inorganic acid compound, preferably selected from at least one of nitric acid, aluminum nitrate, acetic acid and citric acid; Preferably, the amount of the adhesive solvent added is 0.4-10 parts by weight, more preferably 0.6-8 parts by weight, relative to 100 parts by weight of the carrier precursor.
7. The preparation method according to claim 5 or 6, wherein, In step (1), the mixture also includes a solvent and a modifying agent; Preferably, based on 1g of the carrier precursor, the volume of solvent used is 0.6-1mL, more preferably 0.65-0.95mL; Preferably, the modifying agent is a water-soluble compound selected from at least one of La, Zr, Ce and W, and more preferably selected from at least one of lanthanum nitrate, cerium nitrate, ammonium metatungstate and zirconium nitrate; Preferably, the amount of the modifying agent added is 0-15 parts by weight, more preferably 0.8-12 parts by weight, relative to 100 parts by weight of the carrier precursor.
8. The preparation method according to any one of claims 5-7, wherein, Step (1) The first mixing includes dry mixing, kneading and / or rolling; Preferably, the conditions for the first mixing include: a mixing time of 10-80 minutes, more preferably 20-60 minutes; Preferably, the first molding conditions include: a molding temperature of 20-60℃, more preferably 30-50℃; and a molding pressure of 3-10MPa, more preferably 5-8MPa.
9. The preparation method according to any one of claims 5-8, wherein, The second mixing in step (2) includes kneading and / or rolling; Preferably, the conditions for the second mixing include: a mixing time of 20-60 minutes, more preferably 30-50 minutes; Preferably, the conditions for the second molding include: a molding temperature of 30-50°C; and a molding pressure of 5-8.5 MPa. Preferably, the temperature change of the material before and after the second molding is less than 8°C; Preferably, the roasting conditions include: a roasting temperature of 450-1200℃, more preferably 600-1000℃; and a roasting time of 1-8 hours, more preferably 2-6 hours.
10. The preparation method according to any one of claims 5-9, wherein, When the active component is cobalt, the solution containing the active component in step (3) also includes a reducing agent; Preferably, the reducing agent is a water-soluble compound containing a reducing agent component; Preferably, the reducing agent component is selected from at least one of Re, Rh, Pd, Os, Ir, Pt, Ag, and Au; Preferably, the amount of the solution containing the active component is such that, based on the total mass of the catalyst and as oxides, the mass percentage of the active component is 5-18 wt%. Preferably, the amount of the reducing agent is such that, based on the total mass of the catalyst and in terms of elements, the mass percentage of the reducing agent component is 0-0.5 wt%, preferably 0.005-0.3 wt%. Preferably, the calcination conditions in step (3) include: a calcination temperature of 200-500℃, preferably 250-400℃; and a calcination time of 1-12 hours, preferably 2-5 hours.
11. The Fischer-Tropsch synthesis catalyst prepared by the preparation method according to any one of claims 5-10.
12. A method for Fischer-Tropsch synthesis, characterized in that, The method comprises: carrying out a Fischer-Tropsch synthesis reaction on the reactants in the presence of the catalyst described in any one of claims 1-4 and 11; Preferably, the reactants for the Fischer-Tropsch synthesis reaction include H2 and CO; Preferably, the reaction conditions include: a reaction temperature of 170-350℃, more preferably 180-330℃; a reaction pressure of 1-20 MPa, more preferably 1.5-15 MPa; and a volume hourly space velocity of 500-10000 h⁻¹. -1 Preferably 1000-8000h -1 .
Citation Information
Patent Citations
Inner core type cloverleaf-pattern catalyst carrier and preparation method and application thereof
CN105233880A